If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(8b + -4) = -28 Reorder the terms: -7(-4 + 8b) = -28 (-4 * -7 + 8b * -7) = -28 (28 + -56b) = -28 Solving 28 + -56b = -28 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + -56b = -28 + -28 Combine like terms: 28 + -28 = 0 0 + -56b = -28 + -28 -56b = -28 + -28 Combine like terms: -28 + -28 = -56 -56b = -56 Divide each side by '-56'. b = 1 Simplifying b = 1
| x^2+4x+8=2x-1 | | -4(7+p)=-44 | | 6b^2-96-7=0 | | 18=x-(1/4x)-1/2 | | 4x+7=133 | | 2x^3-12x^2=-17x | | 13b=234 | | f(t)=-16t^2+20t | | 4x-17=2x+7 | | 6(x+3)=2(x+3)+12 | | 2/4=3/b | | 12x+9=8x-2 | | 1.5y-6=9.4-y | | 7/9x3/4 | | 25x=1.05 | | m/2=6/8 | | E=3n-4 | | 4(3x+x)+7-5x=(-5)(5x-6x)+23 | | C=1.75+.95(15-3) | | 4z/7=-3 | | 5a-6=11a-33 | | 8/v=4/5 | | 4y^2=1-4x^2 | | 1/2x6/8 | | 6x+30=16x-5 | | 4/2=x/4 | | 4X=5n+3 | | f(-4)=3x^2-4x+4 | | 8x+32=5x+50 | | 27j^4-72j^3+9j= | | 4x+12-3x-12=21 | | 2x+6-4=0 |